Landslide Zone Investigation with Resistivity Method In Jombok Village, Ngantang District, Malang Regency - Pitoyo Widhi Atmoko; Adi Susilo; Arief Rahmansyah (Natural B, Journal of Health and Environmental Sciences, 2012)
Has done research in the Jombok Village, it’s village isone of the areas prone to landslide, this can be seen the existence of land subsidence that has occurred more than once in the same place and of the circumstances surrounding the research that was once a forest area, now used as farmland by human residents. One method used in this research is using geoelectric resistivity method. The data has obtained from geoelectric results, in the entire area has a type of clay and sand, whereas in areas that are kind of soil is a decline in soil, addition of these data, hazardous Jombok Village, Hamlet Songkorejo demonstrated the value of score susceptibility of 3.85, where the value is included in the category of susceptible/prone.